2023
DOI: 10.3390/jcm12020523
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Neuropsychiatric Features of Chronic Migraine Patients during the Interictal Phase

Abstract: This study aimed to examine the presence of neuropsychological deficits and their relationships with clinical, pharmacological, and neuropsychiatric characteristics in chronic migraine (CM) patients assessed during a headache-free period. We enrolled 39 CM patients (mean age: 45.4 years; male/female ratio: 3/36) and 20 age-, sex-, and education-matched healthy controls (HCs, mean age: 45.5 years; male/female ratio: 2/18) in a case–control study. All CM patients underwent a full and extensive clinical, neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…A phase 3 RCT comparing the feasibility and short-term efficacy of mindfulness added to treatment as usual and usual treatment alone for CM patients indicated that adding mindfulness to treatment as usual was feasible with short-term efficacy versus treatment without mindfulness [ 150 ]. A clinical study aimed at examining neuropsychological and neuropsychiatric characteristics of CM patients during the interictal phase concluded that CM patients showed a higher rate compared to healthy controls in cognitive domains (such as sustained attention, information processing speed, visuospatial episodic memory, working memory, and verbal fluency) and depressive and anxiety symptoms [ 151 ]. In a case of CM, the integrated model and the pharmacological options together present beneficial management of the patients.…”
Section: Psychological Therapeutic Options In CMmentioning
confidence: 99%
“…A phase 3 RCT comparing the feasibility and short-term efficacy of mindfulness added to treatment as usual and usual treatment alone for CM patients indicated that adding mindfulness to treatment as usual was feasible with short-term efficacy versus treatment without mindfulness [ 150 ]. A clinical study aimed at examining neuropsychological and neuropsychiatric characteristics of CM patients during the interictal phase concluded that CM patients showed a higher rate compared to healthy controls in cognitive domains (such as sustained attention, information processing speed, visuospatial episodic memory, working memory, and verbal fluency) and depressive and anxiety symptoms [ 151 ]. In a case of CM, the integrated model and the pharmacological options together present beneficial management of the patients.…”
Section: Psychological Therapeutic Options In CMmentioning
confidence: 99%